Peace Building through Peace Language and Civic Peace Training for Students at SMK Telkom Makassar - Asri Ismail; M. Yunasri Ridhoh (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This Community Service Program (PKM) aims to foster awareness and competence among students of SMK Telkom Makassar in building a culture of peace through peaceful language and civic peace training. The training was designed as an applied form of character and citizenship education within the context of a technology-based vocational school. The participatory training method involved discussion, simulation, case reflection, and collaborative projects. The results show an improvement in students’ ability to identify hate speech, transform violent language into peaceful expressions, and enhance their sense of digital citizenship responsibility. Furthermore, students demonstrated higher awareness of empathetic communication and constructive conflict resolution. This program is expected to serve as a model for peace education that can be replicated in other vocational schools.